ATROCITIES WITH A POSITIVE ACCOUNT BALANCE? INCLUDING MEASURES TO RECAPTURE CORPORATE PROFITS DERIVED FROM GROSS HUMAN RIGHTS VIOLATIONS IN REPARATION PROGRAMMES UNDER THE INTERNATIONAL LEGAL FRAMEWORK OF STATE RESPONSIBILITY - Fernández, Rosa Ana Alija (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
Although steps are being made to make companies participate in the redress of the human rights violations they have committed, at the current level of development of international law the obligation to make reparation continues to reside with the States. Indeed, certain legal norms and principles in the general regime of responsibility of the State for internationally wrongful acts would justify – or even require – the adoption of measures to restore the profits obtained by companies as a result of their involvement in the commission of serious violations of human rights. The implementation of such ‘profit recapture measures’ could be better done through large-scale administrative reparation programmes that give effect to the State obligation to redress victims.